Improving the Usability and Effectiveness of FishPath, a Web-Based Decision Support Tool for Data-Limited Fisheries Management - Snouffer, Brian (My University, 2018)
FishPath is a recently created, web-based, decision support tool for data-limited fishery managers. Throughout 2016-17, it has been beta tested at workshops around the world. Feedback from these workshops has expressed the view that while the content of FishPath is good, users have routinely expressed frustration at the lack of usability and difficulty of synthesizing the results into decision support. This project designed and developed software features for FishPath that will address these concerns. The new features allow for user interaction with the results in order to perform and document the decision making process within FishPath itself. To facilitate easier dissemination of results, a reporting function has also been added. This includes two summary report formats, as well as provides a framework within the software for the creation of additional reports.
Thesis (Master's)--University of Washington, 2017
Keywords: Data-Limited Fisheries; Decision Support; Fisheries Management; Software; Technology; Natural resource management; Marine affairs